Patient and Caregiver Need: Utilization of Home Health Care Nursing And Outcomes of Care in Patients with Disability - Sreeprasarn, Phatcharakoraphot; Ckumdee, Sineenuch (Journal of Public Health Nursing, 2018)
With an increased number of chronic illnesses and disabilities, home care has become more significant as a replacement for hospital care. This study was designed to explain patient and caregiver needs and the relationships between utilization of home health care nursing and outcomes of nursing care in patients with disability. This retrospective study analyzed data from the Ramathibodi Home Care Data Set (RHDS). A purposive sample of 221 cases was selected using inclusion criteria of patients who had a Katz’s Index of Independence in Activities of Daily Living Score (ADLs) of 7 points. The Cronbach's alpha coefficient of the ADLs was .91, Peason's product moment correlation coefficient was used to analyze the relationships between home health care provision and outcomes of care at a statistical significance level of .01 Results assessing the needs of patients and caregivers showed self-care and knowledge deficits of 95.9% and 81.9%. Clinical problems encountered included activity intolerance, alteration of nutrition and ineffective airway clearance at 80.1%, 54.8% and 38.0% respectively. Risk for injury and infection were 82.4% and 65.6%. Provision of home health care nursing included 1 - 15 visits with an average in each case of 2 visits. Hospital outcomes of care were discharge to home (45.7%), death at home or hospital (40.7%) and re-hospitalization (12.2%). The relationship between home health care provision and outcome of care at discharge from the home health care unit is statistically significant (r=.216, p < 0.01). Findings show that needs of patients and caregivers are important and that home health care nurses should prioritize nursing interventions to improve outcomes of care. Results of this study have implications for nursing practice for patient and caregiver needs where unstable conditions put disabled patients at risk of re-hospitalization. Further study is recommended to analyze the multidimensional factors involved in patient and caregiver needs and outcomes of care in order to develop continuing quality improvement to prevent patient readmission.